HUBUNGAN AKTIVITAS FISIK DAN POLA MAKAN PADA SINDROM METABOLIK MAHASISWA - Khair, Fahmi Bil; Harvianto, Yudo (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2021)
Epidemiological data states that 23.34% of the total population has metabolic syndrome 26.2% in men and 21.4% of women. Based on observations made, the habit of students not doing breakfast before the lecture is carried out, in addition, in everyday life students often consume sweet and fatty foods, as well as lack of physical activity outside of lectures. Based on the background above, researchers will examine the Relationship of Physical Activity and Diet in Metabolic Syndrome of PJKR FKIP UPR Students in 2021. The goal of this study is to find out the relationship of physical activity and diet in the metabolic syndrome of students at PJKR FKIP UPR in 2021. This research is descriptive research. Data collection techniques with observation, questionnaires and documentation. The sample number in the study was 153 students. The statistical test used is the Pearson Correlation Test. The results showed that there was no meaningful association between physical activity and diet to metabolic syndrome. The conclusion of this study is that there is no meaningful relationship between diet and physical activity against metabolic syndrome. And diet and physical activity are not a factor in the risk of metabolic syndrome.